Heterogeneous Photocatalytic Degradation of Ibuprofen Over TiO2–Ag Supported on Activated Carbon from Waste Tire Rubber (2020)
In recent years it has been discovered that some common use medicines, such as ibuprofen and other nonsteroidal anti-inflammatory drugs, are found in water sources in concentrations that have the potential to affect aquatic organisms. On the other hand, waste used tires are a massive problem for the environment due to the leaching of toxic compounds to soils and water. Also, the exposition to environmental conditions can make them sources of vectors like mosquitoes. In this work, three activated carbon (AC) catalysts derived from waste tire rubber, titanium dioxide and silver were synthesized using the sol–gel method. Morphological characterizations such as SEM and TEM were performed in which, the agglomeration of titanium particles and silver crystals on the surface of the AC is evident. In the XRD analysis, the presence of elemental silver nanoparticles was detected. In the diffuse reflectance spectroscopy analysis, the decrease in the titanium band gap, as well as activity in the visible spectrum, was observed. The photocatalytic tests were performed at pH 3 and 7 in the presence of UV/Vis radiation. These tests show that there are differences between the catalyst in both, UV and visible regions. Adsorption is a major phenomenon for the removal of ibuprofen, followed by photolytic decomposition. In visible spectra, the catalysts show a good performance for the removal of ibuprofen.